Relation between maternal haemoglobin concentration and birth weight in different ethnic groups. - Steer, P. (BMJ Group, 1995)
OBJECTIVE--To assess the relation of the lowest haemoglobin concentration in pregnancy with birth weight and the rates of low birth weight and preterm delivery in different ethnic groups. DESIGN--Retrospective analysis of 153,602 pregnancies with ethnic group and birth weight recorded on a regional pregnancy database during 1988-91. The haemoglobin measurement used was the lowest recorded during pregnancy. SETTING--North West Thames region. SUBJECTS--115,262 white women, 22,206 Indo-Pakistanis, 4570 Afro-Caribbeans, 2642 mediterraneans, 3905 black Africans, 2351 orientals, and 2666 others. MAIN OUTCOME MEASURES--Birth weight and rates of low birth weight (< 2500 g) and preterm delivery (< 37 completed weeks). RESULTS--Maximum mean birth weight in white women was achieved with a lowest haemoglobin concentration in pregnancy of 85-95 g/l; the lowest incidence of low birth weight and preterm labour occurred with a lowest haemoglobin of 95-105 g/l. A similar pattern occurred in all ethnic groups. CONCLUSIONS--The magnitude of the fall in haemoglobin concentration in pregnancy is related to birth weight; failure of the haemoglobin concentration to fall below 105 g/l indicates an increased risk of low birth weight and preterm delivery. This phenomenon is seen in all ethnic groups. Some ethnic groups have higher rates of low birth weight and preterm delivery than white women, and they also have higher rates of low haemoglobin concentrations. This increased rate of "anaemia," however, does not account for their higher rates of low birth weight, which occurs at all haemoglobin concentrations.